AI-Based development on software ecosystem platforms - Silva, Izaque; Gomes, Jonas; Braga, Regina; David, José Maria N.; Stroele, Victor; Soares, Rômulo; Oliveira, Vitória; Oliveira, André Luiz De (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Recent advances in machine learning have stimulated interest in integrating Artificial Intelligence (AI) capabilities into large-scale software and services. However, the support of Software Engineering (SE) methods and tools did not go along with this evolution. Therefore, the SE community needs improved methods and tools to support this new reality. The development of AI-based applications involves many challenges. One of these challenges is to deal with data management. In this paper, we discuss some of the challenges faced by our group in evolving a previous ecosystems platform, to support the development of intelligent applications using Machine Learning (ML) techniques. Our findings drive providing services for data and intelligent algorithms management.